Effectiveness of POGIL Learning Model with Ethnomathematics Nuance Assisted by Student Worksheet toward Student Mathematical Communication Skill - Farda, Hilyatin; Zaenuri, Zaenuri; Sugiarto, Sugiarto (Unnes Journal of Mathematics Education, 2017)
The purpose of this study was to analyzing the effectiveness of POGIL model learning with ethnomathematics nuance by using student worksheets towards student’s mathematical communication ability in quadraliteral materialand. The population in this research was the students of seventh grade Junior High School 1 Welahan on year 2016/2017. By using simple random sampling, the selected samples were VII-A as control class with PBL model learning and VII-B as experiment class with POGIL model learning with nuance ethnomathematics by using student worksheet. The methods which have been used to collect data were documentation, test, and questionnaire. Data were analyzed using proportion test, independent samples t-test, and linear regression. The result of research showed that (1) Student’s mathematical communication ability which have studied with POGIL model learning with ethnomathematics nuance by using student worksheets reach the minimum score criteria, (2) The average of student’s mathematical communication ability by implementing POGIL model learning with ethnomathematics nuance by using student worksheets better than the average of student’s mathematical communication ability by implementing PBL model learning, (3) Respect to local culture attitude influenced toward mathematical communication ability with the number 55,5%.